Lig-8, a Bioactive Lignophenol Derivative From Bamboo Lignin, Protects Against Neuronal Damage In Vitro and In Vivo - Yasushi Ito; Masamitsu Shimazawa; Yukihiro Akao; Yoshimi Nakajima; Norio Seki; Yoshinori Nozawa; Hideaki Hara (Elsevier, 2006)
Lig-8, a lignophenol derivative from bamboo lignin, potently suppresses oxidative stress-induced apoptosis. Here, we first examined in vitro whether lig-8 protects against neuronal damage induced by oxygen-glucose deprivation (OGD) followed by reoxygenation, tunicamycin [endoplasmic reticulum (ER)-stress inducer], or PSI (proteasome inhibitor). In pheochromocytoma (PC12) cell cultures, lig-8 (1 to 30 µM) concentration-dependently inhibited OGD- and tunicamycin (2 µg/ml)-induced cell deaths (significant at ≥3 µM and ≥1 µM, respectively). In human neuroblastoma (SH-SY5Y) cell culture, the PSI-induced apoptotic cell death and fusion protein accumulation (revealing reduced proteasome activity) was inhibited by lig-8 (30 µM). On the other hand, lig-8 at 30 µM alone did not affect any proteasome activity under resting conditions. In vivo, lig-8 (0.1 nmol/eye) reduced intravitreal N-methyl-D-aspartate (NMDA, 20 nmol)-induced retinal damage (decreases in retinal ganglion cells and inner plexiform layer thickness). Hence, lig-8 protects, partly by inhibiting excessive ER-stress, against neuronal damage in vitro and in vivo. Keywords:: lignin, lig-8, retinal ganglion cell, proteasome, endoplasmic reticulum stress